Efeitos do veneno de Lachesis acrochorda em parâmetros cardiovasculares em ratos e em células sanguíneas humanas - Camilo, Karen Leonor Angel (2020)
In Colombia, the Lachesis acrochorda snake is involved in 2-3% of snakebites, characterized by a high mortality rate (90%) due to several blood and cardiovascular complications. In this work, some blood effects of the snake venom L. acrochorda (SVLa) were evaluated in human blood cells obtained from volunteers. Effects on cardiovascular parameters were evaluated in rats. SVLa induced coagulation and platelet aggregation whose magnitude was comparable to that of the positive control adenosine diphosphate (ADP), being observed more quickly the higher the concentration of SVLa. The aggregating effects of SVLa were significantly inhibited (p <0.05) by acetylsalicylic acid (AAS, cyclooxygenase inhibitor), clopidogrel (CLO, ADP receptor inhibitor), but mainly by Na2-EDTA (Ca2 chelator + metalloproteinase inhibitor) ) and 4- (2aminoethyl) benzenesulfonyl fluoride hydrochloride (AEBSF, serine proteases inhibitor). According to the methods of reducing tetrazole MTT salt and lactate dehydrogenase (LDH) levels, the cell viability of neutrophils and platelets was not altered by SVLa (4 µg/mL), a concentration that did not increase myeloperoxidase activity stimulated in neutrophils with phorbol myristate acetate (PMA). ). In the isolated right atrium of rats, SVLa increased slightly but significantly (p <0.05) the magnitude of spontaneous contractions in the concentration range from 1 to 30 μg/mL. In isolated rat aorta, SVLa significantly relaxed at concentrations greater than 300 μg/mL preparations contracted with KCl or phenylephrine. In vivo, SVLa (0.5 and 1.5 mg/kg, i.v.) induced hypotension and bradycardia, with detection of hemorrhage with lung and kidney damage. Together, our findings allow us to conclude that, under experimental conditions, SVLa manifested coagulation, hypotension and bradycardia. Part of the effects presented here seems to result from the presence of SVMPs and SVSPs in the composition of SVLa.